Repeated Daily Use of Dual-Light Antibacterial Photodynamic Therapy in Periodontal Disease-A Case Report - Katherina Trujiilo; Ismo T. Räisänen; Timo Sorsa; Tommi Pätilä (MDPI AG, 2022)
Good oral hygiene at home is the foundation for optimal treatment response and long-term periodontal disease control. Antibacterial photodynamic therapy (aPDT) provides a very potent adjunctive treatment for plaque control. However, the literature regarding repeated aPDT use is sparse. aPDT has been a modality applied mainly in the dental office environment, and when applied once a year or every few months, the results have been usually disappointing. Recently, LED development has brought aPDT for repeated and practical use at home. We present the very positive results and clinical outcome of daily applied dual-light aPDT-technology treatment in conjunction with mechanical cleaning of a 78-year-old male patient with severe periodontal disease (Stage IV and Grade B).